Can Socratic dialogue techniques be used to increase meaning of life for students with disabilities? - Barida, Muya; Hana, Intan; Widyastuti, Dian Ari (Psychology, Evaluation, and Technology in Educational Research, 2024)
This research was motivated by the low meaningfulness of life among people with disabilities, especially those with autism spectrum disorder with visual impairment (ASDVI). The meaning of life greatly influences a person's quality of life, enthusiasm for living life, productivity, creativity, and happiness in living their own life. So, this research aims to determine the efficacy of individual counseling services using the cognitive behavior therapy (CBT) approach and Socratic dialogue techniques to increase the meaning of life in ASDVI students. The type of research that the researcher applied was a single-subject research experiment with the A-B-A pattern. The subject of this research was an ASDVI student at SLBN 001 Tanjungpinang. The instruments used in this research were observation and interviews. The data analysis method used is the explanatory sequential design. The results of the research showed that there was an increase in the meaning of life in ASDVI students, so the Socratic dialogue technique was considered effective in increasing the meaning of life in someone with disabilities, especially ASDVI specifications. The increasing meaningfulness of life for ASDVI students shows the difference between negative and positive thought patterns. This can be seen in changes in thinking patterns and behavior as well as independence, which shows that ASDVI students have the enthusiasm to live their lives and are independent, and can be active in seeking the views of the general public to achieve the ASDVI students' version of meaning itself and achieve a new, more positive perspective.